Prospective behavioral study colic sutures versus mesh polyglactin 91 O prosthetics - Fernández Naone, Gonzalo; Araújo, Ricardo; Riveiro, María del C; Paganini, Juan J; González, Daniel; Crestanello, Juan; Andreoli, Gustavo (Cirugía del Uruguay, 1996)
A prospective, randomized study was carried out in arder to study the incidence of a prosthetic mesh of polyglactine 91 O over scarring of colon sutures. 30 whites rats were operated on and divided into 2 groups: a control one in which the colic suture was apposed to the anterior parietal peritoneum and a study one in which it was apposed to a polyglactine 910 prosthetic mesh.